SOC 2018 - Witt, John (New York, NY : McGraw Hill, 2018)
Connect also comes with LearnSmart, an adaptive questioning tool proven to increase content comprehension and student results, as well as fun interactivities like In their Shoes and Applying the Perspectives that teach sociology's three theoretical frameworks.
The sociological imagination -- Sociological research -- Culture -- Socialization -- Social structure and interaction -- Deviance -- Families -- Education and religion -- Economy and politics -- Social class -- Global inequity -- Gender and sexuality -- Race and ethnicity -- Population, health, and environment -- Social change
Includes bibliographical references and indexes.
ESS
STS International
Keywords: Sociology Textbooks; Sociology Research; Sociology; Textbooks